Pengembangan Buku Pegangan Guru untuk Pembelajaran Kimia Terintegrasi Ayat-ayat Al-Qur’an - Abdul Mujala; Muhammad Reza; Kana Puspita* (Universitas Syiah Kuala, 2022)
Since curriculum 2013 place spiritual aspect into core competences, it supported to enhance students’ behavior. Due to its new implementation, teachers did not get sufficient learning materials to integrate spiritual context in teaching process. This research aims to develop handbook integrated with Alquran for teachers in chemistry learning. To develop the handbook, it used research and development (RD) method combined with ADDIE model. The population was chemistry teachers among senior high school in Banda Aceh, whereas the sample was four chemistry teachers from SMA Fatih Billingual School Banda Aceh, SMAN 3 Banda Aceh and MAN 1 Banda Aceh. To assess the quality of product, the quality control and assessment sheet were distributed to experts. Before that, need analysis was done to observe teacher expectation and hopes. Then, the result showed that almost 90% of samples confirmed positively to the handbook requirement. At implementation stage, several experts gave good marks which was 3.29 out of 4.00. In addition, the responses of teachers supported with about 90% and 80% of positive responses, respectively. Therefore, it can be concluded that the development of handbook was overall good based on assessment given by experts and responses delivered by teachers and students.